SELECTION OF SWEET PEPPER ON STABILITY TO DISEASES IN CONDITIONS OF TRANSNISTRIA - E. S. Demidov; O. P. Bronich; A. A. Kushnarijov; O. N. Shlijomka; I. V. Kropiviyanskaya (Овощи России, 2018)
Pepper (Capsicum annuum L.) is an economically significant nightshade culture in many countries, including Transnistria. On the basis of the State Institution "Transnistrian Institute of Agriculture" in conditions of open ground on a long-term provocative background of monoculture of nightshade, the study of various diseases of sweet pepper is conducted, the allocation of resistant plants for further selection work on the creation of specialized varieties and F1 hybrids with high genetic potential and resistant to stressful environmental factors. In 2016-2017 the selection material for selection of sweet pepper for resistance to major diseases (verticillosis, yellow wilting, or phytoplasmosis and viral pathogens) was studied. The best selection samples were selected for the complex of features. According to the total yield, Positron variety was significantly superior to the standard by 13% and L-70 sample by 19%. A complex phytopathological evaluation showed that the L-70 sample was very poorly affected by verticillium fading, and yellow fading and viral diseases - to a weak degree. The Positron variety was characterized by a mild disease defeat. The degree of development of verticillosis in general in the nursery was weak and varied from 6,8 (L175) to 11,4% (L-144), the development of yellow wilting – from weak to medium – 22,2-41,5%, and the damage caused by virosis varied within the limits of 16,2-33,7%. The most harmful were phytoplasmic diseases, which manifested themselves mainly in the form of yellow wilting and to a lesser extent – a typical stalk caused by phytoplasm PhLO. Thus, in the competitive test, a sample L-70 with a high yield of commercial fruits and a minimal disease affection in a complex phytopathological assessment was identified, as well as a Positron variety with a high early and overall yield and a low disease burden. The best indicators of the biochemical composition of fruits, as close as possible to the requirements of the canning industry, were samples of L-175, L-134, L-144 and Positron variety.